2021
DOI: 10.1007/s00709-021-01640-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and biochemical studies of Spartium junceum infected by Xylella fastidiosa subsp. multiplex ST 87

Abstract: Spartium junceum L. is a typical species of Mediterranean shrubland areas, also grown in gardens and parks as an ornamental. In recent years in Europe, S. junceum has been recurrently found to be infected by different subspecies and genotypes of the quarantine regulated bacterium Xylella fastidiosa (Xf). This work presents for the first time the anatomy of S. junceum plants that we found, by means of genetic and immunochemistry analysis, to be naturally infected by Xf subsp. multiplex ST87 (XfmST87) in Monte A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Biochemical responses of tannins and suberin have been studied as important factors in protecting living tissues (Danti et al, 2018;Falsini et al, 2022). In the present trials, tannins and suberin highlighted by specific staining reactions were found to be similar in the different pruning cut methods examined.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Biochemical responses of tannins and suberin have been studied as important factors in protecting living tissues (Danti et al, 2018;Falsini et al, 2022). In the present trials, tannins and suberin highlighted by specific staining reactions were found to be similar in the different pruning cut methods examined.…”
Section: Discussionmentioning
confidence: 48%
“…As a practice to protect pruning wounds, up to now technical operators report that pruning cuts made over the basal buds on canes prevent wood necroses, especially if a stub ("legno di rispetto" in Italian, or "chicot" in French) is left at each pruning site (Simonit, 2013). However, no histological observations have been made on grapevine tissues react to produce physical barriers or active defence substances (i.e., tannins and phenols; Falsini et al, 2022), that potentially prevent pathogen entry and colonization.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial wall is in strict contact with the host cytoplasm and lipid bodies, suggesting a possible interaction between the endophyte and the host. Pathogenic endocellular bacteria can rarely be visualized in plants, since plant cells tend to undergo a fast death, either due to pathogenicity itself or programmed cell death, as in the case of Xylella infection of Spartium junceum , where the bacterium can be visualized almost exclusively in the xylem elements [ 45 ]. Intracellular bacteria surrounded by a wall can be observed also as a result of phagocytosis in intestinal epithelial cells, as in Figure 2 and Figure 3 in the work of Yamauchi et al (2000) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whichever grafting method is applied, a successful graft union must initially repair the mechanical damage caused by the grafting wounds. In this stage, the physical and antimicrobial barrier at the injured site consists of the accumulation of polymerized phenolic compounds such as suberin and lignin ( Falsini et al, 2022 ). On the metabolic level, defense responses such as the production of pathogenesis-related proteins are induced and expressed by the combination of an oxidative stress and a wound-related hormone signaling ( Loupit and Cookson, 2020 ).…”
Section: Introductionmentioning
confidence: 99%